Development of an Electronic Archive System Application (Star App) as Archival Learning Media at IPIEMS Vocational High School Surabaya City - Jannah, Kunuzil; Wulandari, Siti Sri; Hariyati, Hariyati (Electronic Journal of Education, Social Economics and Technology, 2024)
In accordance with the skills needed by human resources in the 21st century, education is one of the steps to be able to improve these skills. Learning implemented in schools is expected to be able to develop students' skills, one of which is in the use of information technology. In the world of education, electronic records management is one of the important competencies, especially for SMK students majoring in Office Management and Business Services (MPLB). However, observations at SMK IPIEMS Surabaya show that learning electronic records management has not been optimal. The use of Microsoft Access as learning media has various limitations, so that more than 50% of students are not yet skilled in electronic records management. For this reason, technology-based learning media such as the web-assisted electronic archive system application (Star App) is required. Star App is designed to facilitate students in practising electronic archive management, including data entry, archive retrieval and archive retention. This application is equipped with electronic archive theory material that makes it easier for students to understand concepts and practices. Previous research proves that web-based learning media is effective in improving student learning outcomes and skills. Thus, the development of Star App is expected to improve the quality of electronic archiving learning and students' skills in facing the challenges of the digital era.